A NEW SEQUENCE SPACE DEFINED BY A MODULUS - Altin, Yavuz; Isik, Mahmut; Colak, Rifat (Univ Babes-Bolyai, 2008)
The idea of difference sequence spaces was introduced by Kizmaz [8] and this concept was generalized by Et and Colak [6]. In this paper we define the space l(Delta(m), f, p, q, s) on a seminormed complex linear space by using modulus function and we give various properties and some inclusion relations on this space. Furthermore we study some of its properties, solidity, symmetricity etc.
Keywords: difference sequence; modulus function